2017
DOI: 10.1038/s41598-017-06450-2
|View full text |Cite
|
Sign up to set email alerts
|

Urinary concentrations of phthalate metabolites in early pregnancy associated with clinical pregnancy loss in Chinese women

Abstract: Limited evidence revealed conflicting results on relationship between phthalate exposure and clinical pregnancy loss (gestational weeks >6). A prospective cohort study in Chinese pregnant women (n = 3220) was conducted to investigate the association between urinary phthalate metabolites and clinical pregnancy loss (gestational weeks 6 to 27; n = 109). Morning urine samples during gestational weeks 5 to 14 (mean 10.42) were collected to measure monomethyl phthalate (MMP), monoethyl phthalate (MEP), monobutyl ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 60 publications
2
15
1
Order By: Relevance
“…Bottlenose dolphin exposure to DEHP and DEP is concerning due to laboratory and human studies linking these chemicals to adverse health effects including altered hormone synthesis and transport (ATSDR, ; Meeker & Ferguson, ; Sathyanarayana et al, ], male genital developmental abnormalities (ATSDR, ; Swan, ), reproductive impairment (e.g., lower birth weight, Messerlian et al, ; preterm birth, Meeker et al, ; delayed time to pregnancy, Thomsen et al, ; pregnancy loss, H. Gao et al, ), and liver toxicoses including liver cancer (ATSDR, ). In fact, MEHP concentrations measured in the dolphins in this study (GM = 1.9 ng/ml; Range = 0.9–5.9 ng/ml) were at comparable levels reported to be associated with a reduced probability of reproductive success in humans (Hauser et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Bottlenose dolphin exposure to DEHP and DEP is concerning due to laboratory and human studies linking these chemicals to adverse health effects including altered hormone synthesis and transport (ATSDR, ; Meeker & Ferguson, ; Sathyanarayana et al, ], male genital developmental abnormalities (ATSDR, ; Swan, ), reproductive impairment (e.g., lower birth weight, Messerlian et al, ; preterm birth, Meeker et al, ; delayed time to pregnancy, Thomsen et al, ; pregnancy loss, H. Gao et al, ), and liver toxicoses including liver cancer (ATSDR, ). In fact, MEHP concentrations measured in the dolphins in this study (GM = 1.9 ng/ml; Range = 0.9–5.9 ng/ml) were at comparable levels reported to be associated with a reduced probability of reproductive success in humans (Hauser et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A Danish prospective cohort study ( n = 128) reported that maternal urinary MEHP concentrations measured on the 10th day of the last menstrual period before conception were positively associated with subclinical embryonic loss (<6 weeks' gestation), but inversely associated with clinical pregnancy loss (>6 weeks of gestation) ( 59 ). However, in a large population study ( n = 3,220), maternal urinary concentrations of MEP, MEOHP, MEHHP, and ΣHMWP were significantly correlated to higher odds of embryonic loss (during 6–10 weeks' gestation), and MEHHP was positively associated with fetal loss (during 11–27 gestational weeks) after stratified analysis by gestational weeks ( 60 ). With respect to subfertile couples conceiving through medically assisted reproduction, urinary concentrations of DEHP metabolites (MEHP, MEHHP, MEOHP, and the molar sum of DEHP metabolites) during fertility treatment cycle were positively associated with both subclinical embryonic loss and pregnancy loss before 20 gestational weeks ( 63 ).…”
Section: Prenatal Phthalate Exposure and Pregnancy Lossmentioning
confidence: 93%
“…Phthalate exposure may affect pregnancy maintenance and cause pregnancy loss because of the endocrine disruption. Most epidemiologic evidence showed phthalate exposure was related to higher odds of pregnancy loss not only in couples conceiving naturally (59)(60)(61)(62) but also among women undergoing medically assisted reproduction (63) ( Table 3).…”
Section: Prenatal Phthalate Exposure and Pregnancy Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…2018), preterm birth (Ferguson et al. 2014), pregnancy loss (Gao et al. 2017b), and altered neurodevelopment in infants (Engel et al.…”
Section: Introductionmentioning
confidence: 99%